Mites and ticks (Acari) in Shanxi Province, China: an annotated checklist - Ma, Min; Li, Sheng-Cai; Fan, Qing-Hai (Zootaxa, 2015)
This paper reviews the research on mites and ticks in Shanxi Province before 1 January 2015. We provided a checklist of 189 species belonging to 4 orders—Ixodida: 24 species in 2 families and 9 genera; Mesostigmata: 74 species in 12 families and 34 genera; Sarcoptiformes: 17 species in 10 families and 14 genera and Trombidiformes: 74 species in 15 families and 47 genera. Information on the host/habitat and distribution is given for each species. Historical mistakes in records are corrected and the classification of the known species is updated.